Los servicios de orientación en los países de la U.E. - Malik Liévano, Beatriz; Ballesteros Velázquez, Belén (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 1999)
This article surveys the countries of the European Union within the area of orientation. It studies common aspects such as location, focus, financing, and specific, characteristics within each of the 15 member countries of the E.U. through all the different levels of education and administration in the world of orientation and tutoring.